Is it possible to identify physical-motor profiles of preschool children on their association with selected biosocial factors? - Gil-Madrona, Pedro; Losada-Puente, Luisa; Mendiri, Paula; Sá, César; Silva, Inês P.; Saraiva, Linda (Frontiers in Psychology, 2024)
Biosocial factors play a crucial role in the physical-motor development (PMD) of children during the preschool age. The present study aims to identify physical-motor profiles throughout preschool age (3–6 years) and explore associations between profiles and selected biosocial factors such as age, sex, prematurity, weight, height, BMI, and participation in extracurricular physical activities. Data from 412 typically developing children (46.6% girls and 53.4% boys), aged 35–71 months (M = 51.21, SD = 10.47) was collected using the Psychomotor Activities Checklist and specifically the scale of Psycho-Motor Aspects. Cluster analysis made it possible to define four different childhood PMD profiles. High PMD; High PMD except left laterality; medium-low PMD; and low PMD. High PMD profile includes older children, with anthropometric measurements closer to the WHO recommendations, fewer preterm children, and greater participation in extracurricular physical activities. Low PMD profile includes younger children, with weight slightly above and height slightly below the WHO recommendations and low participation in extracurricular physical activities. This study allows us to identify specific trends that may be decisive for the motor development of children throughout preschool age, highlighting selected biological variables and participation in extracurricular physical activities.